Etyczny wymiar makroekonomicznych konsekwencji przemian demograficznych - Michalski, Michał A. (Humaniora. Czasopismo Internetowe, 2025)
The article presents an attempt to present an ethical perspective on the way demographic processes affect macroeconomic phenomena. Within the research in the area of ethics of economic life (business ethics), situated in the stream of research on economic culture, attempts have been made from the beginning to study the influence of norms, values and beliefs on the course of economic phenomena and processes. In the current context, when the literature and discussions on socio-economic development indicate and analyze the dimension of macroeconomic consequences of demographic processes more and more clearly, it seems reasonable to include this subject in the issues that are in the spectrum of interest of business ethics. The article presents, among others, theories from the field of economics on the relationship between demographic phenomena and the economy, as well as arguments and positions present in the area of population ethics regarding the assessment of various types of population policies.